1996
DOI: 10.1007/bf01411166
|View full text |Cite
|
Sign up to set email alerts
|

Brain oedema in patients with intracranial meningioma

Abstract: The authors analysed the correlation between different clinical, radiological, and pathological variables and the presence and intensity of brain oedema associated to intracranial meningioma in 400 consecutive patients studied by computerized tomography (CT). The following factors did not show significant correlation with brain oedema development: the age and sex of the patient, the occurrence of focal deficits, the presence of skull changes (endostosis, exostosis, osteolysis), the occurrence of tumour calcifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(31 citation statements)
references
References 50 publications
2
27
1
1
Order By: Relevance
“…1,36,8,9,11,12,1822,25,26,2830,3538,40,41,43,48,51–53,55,59,60, 6264,6870 All investigations were retrospective observational case series, and no prospective controlled trials were identified.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1,36,8,9,11,12,1822,25,26,2830,3538,40,41,43,48,51–53,55,59,60, 6264,6870 All investigations were retrospective observational case series, and no prospective controlled trials were identified.…”
Section: Resultsmentioning
confidence: 99%
“…Brain edema is found in between one-third to two-thirds of intracranial meningiomas, and several previous studies have observed a relationship between edema and epilepsy. 5,11,29,37,38 Vasogenic peritumoral edema in meningioma is believed to be related to angiogenesis and increased pial blood supply, and has been associated with increased expression of vascular endothelial growth factor, metallo-proteinases 2 and 9, and aquaporins 4 and 5. 27,34,45–47,50,65,67 Two studies found edema to be most common with convexity or parasagittal meningiomas, 11,38 but another did not observe a relationship to location, 29 and no consistent association between edema and tumor size or pathological subtype is present across studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many factors have been proposed regarding the development and degree of meningioma-induced brain edema, including tumor size, histological subtypes, tumor vascularity, venous stasis, type of arterial supply (pial or dural predominance), sex hormone receptors, effect of vascular endothelium growth factor, secretory activity, ischemia and true brain invasion. [20][21][22][23][24][25][26][27][28][29] Some investigators have found no significant correlation between histological subtypes of meningiomas and peritumoral brain edema. 19 that the degree of peritumoral brain edema is more significant in atypical and malignant meningiomas than in typical meningiomas.…”
Section: Discussionmentioning
confidence: 99%
“…It has been described in classical literature the cleft sign on T 2 and the absence of PTE as favorable factors for the resection of meningiomas. 912) …”
Section: Introductionmentioning
confidence: 99%